Computerized control system and interface for flexible micromanipulator control. (August 2015) - Hensel, Nicholas C.; Dunn, Ryan M.; Schrlau, Michael G.
Highlights: A GUI for commercial micro- and nanomanipulators was developed. Multiple control options include point-and-click movement and mouse following. Tip detection using image processing corrects for the manipulator's error. The GUI provides faster and more accurate control even for inexperienced users. Abstract: Micro- and nanomanipulators are essential for a broad range of applications requiring precise micro- and nanoscopic spatial control such as those in micromanufacturing and single cell analysis. These manipulators are often manually controlled using an attached joystick and can be difficult for operators to use efficiently. This paper describes a system developed in MATLAB to control a well-known, commercial micromanipulator in a user friendly and versatile manner through a graphical user interface (GUI). The control system and interface allows several types of flexible movement controls in three-axis, Cartesian space, including single movements, multiple queued movements, and mouse-following continuous movements. The system uses image processing for closed loop feedback to ensure precise and accurate control over the movement of the manipulator's end effector. The system can be used on any electronic device capable of running the free MATLAB Runtime Environment (MRE) and the system is extensible to simultaneously control other instruments capable of serial communication.